(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Robotic Process Automation (RPA) has emerged as a transformative technology for automating repetitive, rule-based tasks, enabling organizations to enhance operational efficiency and reduce human error. When integrated with Pega’s powerful Business Process Management (BPM) and Customer Relationship Management (CRM) platforms, RPA amplifies the capabilities of digital workflows by bridging automation gaps and orchestrating end-to-end business processes seamlessly. This article explores the strategic integration of RPA with Pega, detailing architectural patterns, implementation best practices, and key benefits such as accelerated process execution, improved compliance, and enhanced customer experience. Through real-world examples and practical insights, the discussion highlights how this synergy empowers enterprises to streamline complex workflows, reduce costs, and drive digital transformation initiatives effectively. This comprehensive guide is intended for business leaders, process architects, and technology professionals aiming to leverage combined RPA and Pega solutions to achieve scalable, intelligent automation across their organizations.